PENGARUH VARIABEL MAKROEKONOMI TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA (MELALUI PENDEKATAN MONETER) - Rozi Syaputra; Melti Roza Adry (Universitas Negeri Padang, 2019)
This study aims to find out how the Influence of inflation on financial stability system in Indonesia. The data used are secondary data in the form of time series from 2005:M1 to 2017:M12, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are Inflation, BI Rate, BI-7 Day Repo Rate, Exchange Rate and Financial Stability System. The research methods used are: (1) Multiple Linear Regression Analysis and Ordinary Least Square, (2) Classical Assumption Test. The results of the study show that (1) Inflation does not have a significant and negative effect on financial system stability. This means that inflation has no effect on financial system stability. (2) Exchange rates have a significant effect on Financial System Stability. This means that Exchange Rates have positive effect of Financial System Stability in Indonesia, every Rupiah Exchange Rate against US is depreciated, it will increase Financial System Stability in Indonesia. So it can be said that Financial System Stability is influenced by the appreciation or depreciation of the Rupiah Exchange Rate against US in Indonesia.. (3) Economic Growth has a positive effect on Financial System Stability. This means that every Economic Growth increases, it will increase the financial system stability in Indonesia, (4) The Composite Stock Price Index has a positive effect on financial system stability. Si it can be said that financial system stability is influeced by the strengthening or weakening of the JCI in Indonesia.